Cognitive Ability in Late Life and Onset of Physical Frailty: The Lothian Birth Cohort 1936. Issue 6 (1st March 2017) - Gale, Catharine R.; Ritchie, Stuart J.; Cooper, Cyrus; Starr, John M.; Deary, Ian J.
Abstract : Objectives: To investigate whether poorer cognitive ability is a risk factor for development of physical frailty and whether this risk varies according to cognitive domain. Design: Prospective longitudinal study with 6‐year follow‐up. Setting: Edinburgh, Scotland. Participants: Members of the Lothian Birth Cohort 1936 (N = 594). Measurements: Frailty was assessed at ages 70 and 76 using the Fried criteria. Cognitive function was assessed at age 70, 73, and 76. Factor score estimates were derived for baseline level of and change in four cognitive domains: visuospatial ability, memory, processing speed, and crystallized cognitive ability. Results: Higher baseline levels of processing speed, memory, visuospatial ability and crystallized ability at age 70, and less decline in speed, memory, and crystallized ability were associated with less risk of becoming physically frail by age 76. When all cognitive domains were modelled together, processing speed was the only domain associated with frailty risk, for a standard deviation (SD) increment in initial level of processing speed, the risk of frailty was 47% less (0.53 95% confidence interval (CI) = 0.33–0.85) after adjustment for age, sex, baseline frailty status, social class, depressive symptoms, number of chronic physical diseases, levels of inflammatory biomarkers, and other cognitive factor score estimates; for a SD increment in processing speed change (less decline) risk of frailty was 74% less (RRR = 0.26, 95% CI = 0.16–0.42). When additional analyses were conducted using a single test of processing speed that did not require fast motor responses (inspection time), results were similar. Conclusions: The speed with which older adults process information and the rate at which this declines over time may be an important indicator of the risk of physical frailty.